PEMANFAATAN TEKNIK ASCENDINGDAN DESCENDING SEBAGAI CARA EVAKUASI KEADAAN DARURAT DI BANGUNAN TINGGI LINGKUNGAN KESDM - Yudiana Hadiyat; Leni Nurliana (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2018)
Emergencies in buildings may be fires, earthquakes, falling at high. If such emergency conditions occur in non-tiered buildings then the evacuation process will be much easier than the evacuation process in high buildings. Ministry of Energy and Mineral Resources is one of the ministries that have high buildings in its work unit, which is definitely the potential for a emergencies will be very possible. When a emergencies occurs then an existing emergency response facilities should available and employees understand the evacuation procedure. There should be a way or method of escape from high buildings in addition other then use existing emergency response facilities that is by using rope. This study aims to determine whether ascending and descending techniques in the rock climbing can be applied as an alternative evacuation in case of emergency conditions, while the study method used is descriptive qualitative method. The research deliver that the existing facilities and infrastructure of emergency response condition in KESDM workforce have not been well managed and the employees are lack of knowledge of how to escape from emergencies. This can be seen from the absence of routine check cards of infrastructure, employees and security officers do not have the competence certificate of fire handling class B.